Usability study of the qLabs® FIB: A new point-of-care system for functional fibrinogen testing - Maxence Hureau; Anne-Sophie Bouthors; Lucie Deroo; Anne-Sophie Baptiste; Agnès Le Gouez; Mathias Rossignol; Frederic J. Mercier; Agnès Rigouzzo (Thrombosis Update)
Background: Identification of hypofibrinogenemia is particularly important in obstetrics since this predicts progression to severe Post-Partum Haemorrhage (PPH). Objectives: To evaluate the usability of qLabs® FIB at the bedside of patients with PPH. Methods: The qLabs® FIB test was performed using a drop of whole blood from a citrated laboratory tube sampled from each parturient with PPH >1 L by a trained user. A usability survey was completed by each clinician performing the test. Results: During the evaluation, 101 qLabs® FIB tests were performed. One hundred completed surveys and 58 free comments were collected. Satisfaction was achieved in 84 % of tests. Usability in emergency setting, timeliness of results, and the results display were considered positive. The qLabs® FIB results were obtained in <3 min for concentrations below 3 g/L whilst the median time to paired laboratory results was 60 (20–120) minutes. The lower a patient's fibrinogen level, the faster the qLabs® FIB result. Conclusion: The usability study was the first step in the validation process of the qLabs® FIB point of care device in obstetric settings.